2009
DOI: 10.3390/molecules14010329
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6: A Long Known Compound of Surprising Complexity

Abstract: In recent years vitamin B6 has become a focus of research describing the compound’s critical function in cellular metabolism and stress response. For many years the sole function of vitamin B6 was considered to be that of an enzymatic cofactor. However, recently it became clear that it is also a potent antioxidant that effectively quenches reactive oxygen species and is thus of high importance for cellular well-being. In view of the recent findings, the current review takes a look back and summarizes the disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
167
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(180 citation statements)
references
References 143 publications
2
167
0
11
Order By: Relevance
“…Our results show that E. pusillum has multiple mechanisms to deal with oxidative stress. Vitamin B6 has three forms (pyridoxine, pyridoxal, and pyridoxamine) and is an enzymatic cofactor participating in many biochemical reactions [53]. Recent research showed that vitamin B6 played a critical role in resistance to oxidative stress.…”
Section: The Common Drought-resistant Mechanisms In E Pusillummentioning
confidence: 99%
“…Our results show that E. pusillum has multiple mechanisms to deal with oxidative stress. Vitamin B6 has three forms (pyridoxine, pyridoxal, and pyridoxamine) and is an enzymatic cofactor participating in many biochemical reactions [53]. Recent research showed that vitamin B6 played a critical role in resistance to oxidative stress.…”
Section: The Common Drought-resistant Mechanisms In E Pusillummentioning
confidence: 99%
“…[37][38][39] Pyridoxal (PL) and its 5′ phosphorylated derivative are active forms of vitamin B6 that play a critical role in cellular metabolism and stress response. 40,41 Recent studies have highlighted the importance of the protective role of vitamin B6 in carcinogenesis, especially colon carcinogenesis, by reducing cell proliferation, oxidative stress, NO production, and angiogenesis. 42,43 Our previous study revealed that after internalization, biotin-PLconjugated PAMAM G3 dendrimers had lower cytotoxicity than the nonconjugated forms of the dendrimer in both normal human fibroblasts (BJ) and squamous epithelial carcinoma (SCC-15) cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B 6 (or B 6 vitamer) is one of the essential vitamin compounds involved in many aspects of metabolism in all living organisms (21,22). Vitamin B 6 is the generic name encompassing six biologically interconvertible compounds: pyridoxal (PL), pyridoxine (PN), pyridoxamine (PM), and the phosphorylated forms pyridoxal 5=-phosphate (PLP), pyridoxine 5=-phosphate (PNP), and pyridoxamine 5=-phosphate (PMP) (http://www.chem.qmul.ac.uk/iupac/misc/B6 .html).…”
Section: Discussionmentioning
confidence: 99%